Perkuatan Geser Balok dengan Serpihan Besi untuk Menghemat Tulangan dan Biaya di Era New Normal Setelah Pandemi Covid-19 - LINA, HERLINA SUSILAWATI (Jurnal Proyek Teknik Sipil, 2023)
Damage that occurs in building structures is a problem that often occurs, especially damage to beams. Beams are a very important structural element in buildings. Collapse that occurs in beams is generally caused by shear forces, because collapse caused by shear forces occurs suddenly because concrete is brittle. Handling that can be done one of which can be done by handling the shear reinforcement in the beam with reinforcement so that the beam can withstand the working load. One of the methods used to overcome damage to beams is by providing strength or in the form of mixed materials in the form of flakes/iron filings. The purpose of this study was to determine the effect of beam strength on the shear capacity of reinforced concrete beams. The benefits of this research are expected to contribute to science, in particular to become recommendations for strengthening structures. 6 specimens were used with variations in tensile reinforcement and there were 3 beams that did not use iron flakes/fibers and 3 beams used flakes/iron filings reinforcement. Based on the results of the research obtained, the greater the value of the reinforcement ratio given, the greater the stiffness of the specimen, but the greater the value of the tensile reinforcement ratio given will not affect the shear capacity of a reinforced concrete beam.